Laparoscopic versus laparotomic surgery for adnexal masses: role in elderly. Issue 1 (December 2016) - Pulcinelli, F.; Schimberni, M.; Marci, R.; Bellati, F.; Caserta, D.
Abstract Background The purpose of this study is to compare laparoscopy (LPS) and laparotomy (LPT), in terms of surgical outcomes, in elderly patients (>65 years) with adnexal masses. Methods We retrospectively reviewed a series of women older than 65 who had a diagnosis of adnexal masses. Then, all patients were divided into two different groups according to the type of surgery: 27 who underwent LPS (LPS group) and 24 who underwent LPT (LPT group). We took into consideration: age, comorbidity, histological diagnosis, surgery approach, and surgical outcome. Then, we calculated the percentages of all of these data and thenχ 2 test andt -Student test were used to calculate thep value, to compare the two surgical techniques. Ap value lower than 0.05 was considered to be statistically significant. Results At first, we evaluated the relation between the diagnosis and the surgery approach, and we obtained statistically significant results for serous cyst, adenocarcinoma serous/mucinous, and others, and the table highlights that some of the benign masses were mostly treated with LPS, while borderline and malignant masses were treated with LPT. Then, we evaluated the comorbidities of the patients, and we found that those cases had a significantly higher prevalence of cardiovascular disease and metabolic diseases. Finally, we compared the surgery outcome of LPS versus LPT surgeries for adnexal masses in elderly women, and there were statistically significant results for postoperative complications, number of patients who needed drainage, and number of days of hospitalization after surgery. Conclusions Our results demonstrated that the patients who underwent LPS, compared to the patients who underwent LPT, have better outcomes in terms of postoperative complications (7.4 % with LPS and 37 % with LPT), number of patients who needed drainage (11.1 % with LPS and 62.5 % with LPT), and number of days of hospitalization after surgery, in term of mean (5 for LPS and 10.9 in term of LPT).